Efficient energy transfer in phenyl-ethynyl-linked asymmetric BODIPY dimers. Issue 42 (16th October 2020) - Hewavitharanage, Priyadarshine; Warshawsky, Reuben; Rosokha, Sergiy V.; Vaal, Jason; Stickler, Kelsey; Bachynsky, Dmitriy; Jairath, Neil
Abstract: Three asymmetric boron dipyrromethene (BODIPY) dimers were synthesized via coupling of a BODIPY monomer with a meso -phenyl ethynyl group substituent to the different monomers with an iodine atom at the second position of the BODIPY core. The dimers were characterized by 1 H, 13 C, and 11 B, 19 F NMR spectroscopy and high-resolution mass spectrometry. Density functional theory calculations show minimal conjugation between the two BODIPY units in the dimers due to a large dihedral angle between the BODIPYs and the linker. Absorption and fluorescence measurements of monomeric and dimeric compounds in dichloromethane indicated highly efficient singlet-singlet energy transfer between two BODIPY units (in which the meso-phenyl containing BODIPY unit act as the donor while the other BODIPY unit is the acceptor) and large Stokes shifts. In particular, the dimer with the styryl BODIPY unit absorbs light in a wide range of the spectrum (325 nm–690 nm) with emission in the near IR region. The ethynyl thiophene linked dimer showed the highest ﬂuorescence quantum yield (76%) of all three dimers investigated in this study. Graphical abstract: Image 1 Highlights: Three asymmetric BODIPY dimers with phenyl-ethynyl linkers are synthesized. Efficient energy transfer occurs between nearly orthogonal BODIPY units. Energy transfer enhance the acceptor fluorescence with large Stokes shifts. The dimer with styryl-BODIPY unit shows wide-range (330–690 nm) absorption and NIR emission.